Long-term survival of patients treated for Hodgkin's disease in 1971-1996 depending on the clinical stage of the disease, patient's fertility after therapy and cause of death analysis - Fridrichova, M; Dienstbier, Z; Loucka, M; Skala, E; Blomannova, E (Neoplasma, 2009)
The long-term survival in a group of 370 patients treated for Hodgkin's disease in the years 1971-1996 was retrospectively analyzed. Up to now 191 patients live. 179 patients have died. Since the year 1978 the uniform diagnostic and therapy protocol has been used. The therapy consisted in the combination of a radiation therapy (usual dose 40 Gy) with the COPP chemotherapy (6 cycles). Since the year 1988 the alternation of the ABVD and COPP chemotherapy has been used. According to the stage of the Hodgkin's disease and the patient's age the modification of the therapy was introduced. One chemotherapy cycle was removed for each 10 years above the 50 year age of the patient. The radiation therapy was not applied to the areas of the reproductive organs in young patients to preserve their fertility. The percentage of surviving patients for thirty years was 58.8% for Stage I and IIA,B and for Stage IIIA was 60.72%. In the group of surviving patients, we have registered 11 fathers and 34 females with up to 3 children. All together 75 children without health problems are monitored.
Keywords: Vinblastine; novorozenec; Infant, Newborn; kombinovaná terapie; Vincristine; Humans; adjuvantní radioterapie; Female; lidé středního věku; přežívající; Radiotherapy, Adjuvant; Bleomycin; dítě; Child; bleomycin; doxorubicin; rizikové faktory; dospělí; protokoly protinádorové kombinované chemoterapie; Aged; fertilita; prokarbazin; Doxorubicin; výsledek terapie; Hodgkin Disease; Prednisone; senioři; lidé; Survivors; Time Factors; vinblastin; dakarbazin; časové faktory; Hodgkinova nemoc; Adult; prednison; staging nádorů; ženské pohlaví; Dacarbazine; Male; Middle Aged; vinkristin; Fertility; prognóza; Antineoplastic Combined Chemotherapy Protocols; Treatment Outcome; Cyclophosphamide; Procarbazine; Cause of Death; Neoplasm Staging; příčina smrti; míra přežití; Combined Modality Therapy; mužské pohlaví; cyklofosfamid; Prognosis; Risk Factors; Survival Rate